Novel temperature-sensitive hydrogel for liver cancer TACE treatment
By designing a temperature-sensitive hydrogel, combined with Poloxamer-407 and Fe3O4 nanoparticles, the problems of insufficient embolization intensity and toxicity reaction of existing embolization materials in the treatment of TACE in liver cancer are solved, and stronger embolization effect and better controlled release of drugs.
Patent Information
- Application Number
- CN202411510879.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
AI Technical Summary
The existing embolization materials used for the treatment of TACE in liver cancer have problems such as insufficient embolization strength, high heterogeneity, high inhomogeneity and systemic toxic reactions.
A temperature-sensitive hydrogel was designed to form a composite gel by preparing Poloxamer-407 into a hydrogel and mixing it with Fe3O4 nanoparticles. The hydrogel has a low viscosity at low temperatures, can achieve intravascular embolization in the body, and can reversibly turn into a sol when the temperature rises, avoiding permanent embolization.
It has achieved stronger embolization effect and better controlled drug release in the treatment of liver cancer TACE, reduced systemic toxicity, degradability, is suitable for the local microenvironment of liver cancer, and is conducive to subsequent treatment.
Smart Images

Figure CN119455059A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical technology, and in particular to a novel temperature-sensitive hydrogel for TACE treatment of liver cancer. Background Art
[0002] Transarterial chemoembolization (TACE) is a controlled injection of embolic material into the target artery supplying the tumor through an arterial or intravenous catheter, which occludes the target artery and causes ischemic necrosis of the tumor tissue, thereby achieving the purpose of killing the tumor. For patients with hepatocellular carcinoma (HCC) who cannot receive radical treatment such as liver transplantation, tumor resection or percutaneous radiofrequency ablation, TACE is the core treatment method. The embolic material used in early TACE was super-liquid iodized oil, which has lipophilic characteristics and can emulsify chemotherapy drugs, but its embolic strength is not enough. Therefore, gelatin sponge particles are generally added for embolization after using iodized oil. However, iodized oil is liquid, has weak embolic ability and is easy to diffuse outside the liver, while gelatin sponge has large heterogeneity, and gelatin sponge particles are usually handmade and have uneven characteristics, resulting in poor embolization effect. In addition, the injection time interval between iodized oil and gelatin sponge may also cause iodized oil and chemical to be mixed. The therapeutic drugs diffuse outside the liver, leading to systemic toxic reactions and reduced patient tolerance to anticancer drugs, thus affecting the treatment effect; since then, the use of drug-eluting microspheres has further developed TACE technology. For example, microspheres synthesized from polyvinyl alcohol have good embolization accuracy and drug controlled release, high treatment safety, and few adverse reactions, but they are still non-absorbable. Degradable starch microspheres have also been developed, which have the advantages of positive regulation ability and little impact on the tumor microenvironment, but the embolization strength of this type of microsphere is weaker than that of traditional drug-loaded microspheres, the treatment effect is uncertain, and its application is limited.
[0003] In recent years, with the research and development of more flexible and changeable embolic materials, hydrogels have gradually emerged in clinical applications. Hydrogels are a type of material with a three-dimensional network structure, composed of a large amount of water and a cross-linked polymer network. Its high water content (usually 70-99%) provides the hydrogel with physical similarity to human tissues, good biocompatibility, and the ability to easily encapsulate hydrophilic drugs; and the cross-linked polymer network makes the hydrogel solid and has a wide range of mechanical properties, such as its stiffness can be adjusted between 0.5 KPa and 5 MPa, so as to match different soft tissues of the human body; in addition, it has the ability to change phases affected by multiple factors, good fluidity and in situ gelation ability, and is an excellent drug carrier with stronger drug loading capacity and good controlled release effect. It can even be combined with contrast agents to have better tracing effect and excellent performance. For this reason, if a new embolic material that can be used for TACE treatment of liver cancer can be designed based on hydrogel, it will be conducive to the development of TACE technology. Summary of the invention
[0004] In view of the defects of the prior art, the present invention designs a new temperature-sensitive hydrogel that can be used for TACE treatment of liver cancer.
[0005] In order to achieve the above purpose, the present invention solves the technical problem by adopting the following technical solutions: In a first aspect, the present invention provides an application of a temperature-sensitive hydrogel in the preparation of anti-tumor drugs, contrast agents or vascular embolization products.
[0006] Preferably, the vascular embolization product is a product for treating liver cancer via hepatic arterial chemoembolization.
[0007] Preferably, the raw materials for preparing the temperature-sensitive hydrogel include Poloxamer-407 and Fe3O4 nanoparticles, wherein the particle size of the Fe3O4 nanoparticles is 15nm-20nm.
[0008] Specifically, Poloxamer-407 is a spherical particle form, a high molecular nonionic surfactant, a triblock copolymer composed of polyoxyethylene and polyoxypropylene (70% and 30% respectively), with low toxicity and good biocompatibility. The hydrogel prepared by Poloxamer-407 is a temperature-sensitive reversible gel, which has low viscosity at 4 °C or even at room temperature and is in a sol state. When the temperature rises from 4 °C to the lower critical solution temperature (LCST), it can quickly undergo a transition from sol to gel through the hydrophilic-hydrophobic interaction between polyoxyethylene and polyoxypropylene in the polymer. Its LCST varies according to the concentration and is usually less than 37 °C. And as the temperature drops below the LCST again, this gel reversibly transforms into a sol.
[0009] In a second aspect, the present invention provides a method for preparing a temperature-sensitive hydrogel, comprising: first preparing a hydrogel with a concentration of 10 wt%-20 wt% of Poloxamer-407, and then uniformly mixing it with a Fe3O4 suspension to obtain a composite gel.
[0010] Preferably, the volume ratio of the hydrogel to the Fe3O4 suspension is 1:10.
[0011] Preferably, the Fe3O4 suspension is prepared by suspending Fe3O4 nanoparticles in water with a concentration of 1 mg / mL.
[0012] Preferably, the particle size of the Fe3O4 nanoparticles is 15 nm-20 nm.
[0013] In a third aspect, the present invention provides an injectable material, including the temperature-sensitive hydrogel prepared by the method for preparing the temperature-sensitive hydrogel.
[0014] Preferably, a pharmaceutically acceptable excipient is also included.
[0015] In a fourth aspect, the present invention further provides an embolic agent, comprising the temperature-sensitive hydrogel prepared by the method for preparing the temperature-sensitive hydrogel.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares Poloxamer-407 into a hydrogel and then mixes it with Fe3O4 nanoparticles to obtain a temperature-sensitive hydrogel. By adjusting the concentration and ratio of the hydrogel components, while achieving intravascular embolism, the hydrogel is also degradable and avoids permanent embolism in the blood vessel. This has a positive impact on the local microenvironment of the tumor, is beneficial to subsequent secondary tumor treatment, and also provides a new idea for the development of embolic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 These are scanning electron microscope images of hydrogel Gel and composite gel Fe3O4-Gel.
[0019] Figure 2It is a transmission electron microscope image of Fe3O4 nanoparticles and a statistical graph of their particle size. In the figure: A is a transmission electron microscope image of Fe3O4 nanoparticles; B is a particle size bar graph of Fe3O4 nanoparticles.
[0020] Figure 3 These are actual photos of the morphological changes of hydrogel Gel and composite gel Fe3O4-Gel at different temperatures and the results of temperature sensitivity test. In the figure: A is an actual photo of the morphological changes of the gel at 4 ℃, 37 ℃ and 42 ℃; B and C are temperature sensitivity test pictures of the gel, respectively.
[0021] Figure 4 This is a graph showing the mechanical strength test results of hydrogel Gel and composite gel Fe3O4-Ge.
[0022] Figure 5 The figures are the results of the degradation experiments of hydrogel Gel and composite gel Fe3O4-Ge in vitro and in vivo. In the figure: A is the degradation change diagram of the gel at 37°C in vitro; B is the actual picture of the degradation change of the composite gel Fe3O4-Gel in vivo; C is the angiography of the gel before, after and 2 hours after embolization.
[0023] Figure 6 This is a statistical bar graph of the cytotoxicity test results of the hydrogel: in the figure, A is the hydrogel Gel; B is the Fe3O4 nanoparticles; C is Idarubicin.
[0024] Figure 7 This is a real picture of the coagulation experiment results of hydrogel, in which: A is hydrogel Gel; B is Fe3O4 nanoparticles.
[0025] Figure 8 This is a real picture of the hemolysis experiment results of the hydrogel, in which: A is the hydrogel Gel; B is the Fe3O4 nanoparticles.
[0026] Fig. 9 It is a statistical bar graph of the hemolysis test results of the hydrogel, in which: A is the hydrogel Gel; B is the Fe3O4 nanoparticles. DETAILED DESCRIPTION
[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0029] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0030] like Figure 2 As shown, the particle size of Fe3O4 nanoparticles (purchased from China Neusoft Nanoeast, ordinary spherical nanoparticles, the solvent is ultrapure water, the specification is 1 mg / mL) ranges from 15nm to 20nm.
[0031] The rats used in all experiments of the present invention were SD rats, weighing 300-350 g, purchased from the Animal Center of Sun Yat-sen University.
[0032] Example 1 A novel temperature-sensitive hydrogel for TACE treatment of liver cancer, the preparation method specifically comprising the following steps: 1. Preparation of hydrogel Weigh 2 g of Poloxamer-407 particles according to the mass-to-volume ratio, put them into a centrifuge tube containing 10 mL of sterile deionized water, mix them thoroughly, and place them in a 4°C refrigerator overnight to form a Poloxamer-407 sol with a concentration of 20%, i.e., a hydrogel (hereinafter referred to as Gel), which should be stored in a 4°C refrigerator.
[0033] 2. Preparation of composite gel (at room temperature) Fe3O4 nanoparticles were suspended in sterile deionized ultrapure water to obtain a Fe3O4 suspension with a concentration of 1 mg / mL, which was stored in a refrigerator at 4°C. The Fe3O4 suspension was added to the hydrogel at a volume ratio of 1:10, and the mixture was fully shaken to prepare a composite gel, hereinafter referred to as Fe3O4-Gel, which was stored in a refrigerator at 4°C.
[0034] Example 2 1. The Gel and Fe3O4-Gel prepared in Example 1 were observed using a scanning electron microscope (SEM). Figure 1 shown.
[0035] 2. Thermosensitivity test of gel: 1. The morphological changes of the hydrogel Gel and the composite gel Fe3O4-Gel prepared in Example 1 at temperatures of 4°C, 37°C and 42°C were tested; 2. Prepare Gel with a concentration of 10% according to the hydrogel preparation method in Example 1. Use a rheometer to perform rheological tests on the Fe3O4-Gel composite gels prepared from Gel with concentrations of 10% and 20%. The gel is prepared into a sheet shape with a thickness of 1 mm. The elastic modulus (G') and viscous modulus (G'') in the temperature range of 10 - 40 °C are tested in the compression mode, with a fixed stress of 15 Pa, a fixed frequency of 1 Hz, and a heating rate controlled at 0.1 ± 0.05 °C / s.
[0036] As Figure 3 shown in A, at 4 °C, both Gel and the composite gel Fe3O4-Gel are liquids, and a sol-to-gel transition occurs at 37 °C; as Figure 3 shown in B - 3C, the G' and G'' curves have an intersection point. When G' > G'', it presents a gel state; when G' < G'', it presents a sol state. The appearance of the intersection point indicates the sol-to-gel transition. The sol-gel transition temperatures of the hydrogel Gel and the composite gel Fe3O4-Gel are 20 °C and 25 °C, respectively.
[0037] III. Mechanical Strength Test of the Gel Use a rheometer (Thermo Fisher, USA) to perform mechanical strength tests on Gel and Fe3O4-Gel respectively: Place the two sol samples in the rheometer, test the process of their viscosity change with temperature, and draw curves. Measure the different mechanical strengths of the two gels and record them by drawing curves. Place the hydrogel sample with a thickness of 1 mm between the parallel plates and adjust the plate spacing to 1 mm. Measure the relationship between the storage modulus (G′) and the loss modulus (G″) with temperature (10 - 45 °C), and the test temperature is 37 °C; measure the relationship between G′ and G″ with temperature (5 - 50 °C), and the test conditions are a frequency of 1 Hz and a strain of 0.1%. The temperature corresponding to the intersection point of the G′ and G″ curves is the sol-gel transition temperature of the hydrogel.
[0038] The results are as Figure 4 shown. The mechanical strength of Fe3O4-Gel is much higher than that of Gel and can exceed 0.1 Mpa.
[0039] Example 3 Degradation experiments of the hydrogel in vitro and in vivo: I. Place the 20% concentration Gel and Fe3O4-Gel prepared in Example 1 in PBS buffer solution at 37 °C and observe their degradation情况随时间改变的降解情况。
[0040] II. Inject Gel and Fe3O4-Gel subcutaneously into mice respectively and observe their degradation随时间变化的降解及Fe3O4纳米颗粒的扩散情况。
[0041] 3. In the transcatheter arterialembolization (TAE) treatment of rat orthotopic liver cancer model, DSA angiography was performed before, immediately after and 2 hours after the operation to observe the embolization and degradation of the gel carrier blood vessel. The details are as follows: 1. Construction of an orthotopic rat liver cancer model (1) When N1S1 cells are in the logarithmic growth phase and in good condition, digest, collect, and resuspend in serum-free DMEM medium and adjust the density to 10 7 / mL, keep in ice box for later use.
[0042] (2) Healthy male SD rats aged 12 weeks and weighing 300-350 g that had been fasted for 12 h and deprived of water for 6 h were placed in a small animal gas anesthesia system with an oxygen flow rate of 600 mL / min and an isoflurane concentration of 3% for inhalation gas anesthesia.
[0043] (3) After successful anesthesia, the rat was placed in a supine position with its limbs properly fixed on the operating table. The abdomen was well exposed and the skin was routinely prepared, disinfected, and draped. A longitudinal incision of about 1.5 cm in length was made in the middle of the abdomen below the xiphoid process. The abdominal wall was gently expanded outward with an abdominal wall expander to expose the middle lobe and left lateral lobe of the liver. 200 μL (2×10 6 The needle was inserted from the caudal to the cephalad direction on the inner side of the left lateral lobe of the liver into the liver parenchyma under the liver capsule, and then 200 μL of cell suspension was slowly injected. A round transparent bulge was formed at the injection site. The puncture site was pressed with a cotton swab, and the needle was quickly withdrawn. The cotton swab was pressed for 1-2 min to avoid bleeding from the puncture site and leakage of tumor cell suspension. After confirming that there was no active bleeding in the abdominal cavity, the abdominal wall was sutured in full thickness and the abdomen was closed. Anesthesia was stopped after alcohol disinfection.
[0044] (4) After waking up from anesthesia, the animal can resume eating. After surgery, 20,000 U of penicillin per animal will be injected intramuscularly for 3 consecutive days.
[0045] (5) On the 8th day after tumor cell inoculation, the rats were subjected to MRI plain scan using a GE 3.0T MRI scanner. The coil was a homemade rat coil or wrist coil. After 10% chloral hydrate was injected intraperitoneally to anesthetize the rats, the rats were fixed in a supine position with a homemade fixator. The scanning range was from 5 cm above the diaphragm to the lower pole of the kidney. The scanning sequence was T2WI. The scanning parameters were: TR / TE 2500 / 110 ms, slice thickness 2 mm, slice spacing 0.2 mm, FOV 80× 80 mm, matrix 256×196. The imaging characteristics of in situ HCC in rats were observed. The long diameter of the tumor was measured on the image, denoted as a; the diameter perpendicular to it was denoted as b; the calculation formula was: V = 0.5 × a × b 2.
[0046] 2. Construction of TACE model in rats via gastroduodenal artery puncture and retrograde hepatic artery cannulation (1) SD rats with successfully implanted orthotopic liver tumors were fasted for 12 h and deprived of water for 6 h before surgery. They were placed in a small animal gas anesthesia system with an oxygen flow rate of 600 mL / min and an isoflurane concentration of 3% for inhalation gas anesthesia.
[0047] (2) After successful anesthesia, the rat was placed in a supine position, and the limbs were properly fixed on the operating table. The abdomen was well exposed, and the skin was prepared, disinfected, and draped. The original abdominal surgical incision was made and extended to 4-5 cm in length. The abdominal wall expander was used to expand the abdominal wall outward to completely expose the entire abdominal cavity from the xiphoid process to the pelvic cavity. The tumor in the left lateral lobe of the liver was observed to be single and nodular, with a clear boundary with the surrounding normal liver tissue. The surgical operation was performed under a surgical microscope, the middle lobe and left lateral lobe of the liver were lifted up, the hepatogastric ligament between the papillary lobe and the stomach and duodenum was cut, and the lesser omentum sac and hepatoduodenal ligament were exposed. At this time, the common hepatic artery can be clearly seen to originate from the abdominal aorta and branch into the downward gastroduodenal artery and the upward proper hepatic artery on the left side of the hepatoduodenal ligament. Use an artery clamp to clamp the common hepatic artery; free the gastroduodenal artery, ligate the distal end with 9-0 surgical sutures, and tie a silk thread at the proximal end without ligating for the time being; free the proper hepatic artery and pull it toward the foot side so that it is in a straight line with the proper hepatic artery and maintain a certain tension to facilitate puncture. Puncture the vascular wall with an insulin needle at the proximal end of the gastroduodenal artery and insert it into the gastroduodenal artery, and continue to move forward until it is delivered into the proper hepatic artery. At this time, TAE or TACE operations can be performed. After the operation, slowly withdraw the tube, and before the needle tip is withdrawn, ligate the silk thread reserved at the proximal end of the gastroduodenal artery puncture site to prevent bleeding. Loosen the artery clamp at the common hepatic artery. After confirming that there is no active bleeding in the abdominal cavity, close the abdomen with a full-thickness suture.
[0048] (3) Penicillin 20,000 U / animal was injected intramuscularly for 3 consecutive days after surgery.
[0049] Depend on Figure 5 As shown in A, after 3 h in PBS buffer solution, Gel began to degrade, while Fe3O4-Gel remained in a gel state. Therefore, Fe3O4-Gel has good stability and can be used as an embolic material for animal experiments. Figure 5 As shown in C, before injection, the tumor can be clearly shown in the angiography. After injection, the tumor of the mouse injected with Fe3O4-Gel is basically invisible in the angiography, indicating that Fe3O4-Gel has a good embolic effect as an embolic material.
[0050] Example 4 Cytotoxicity assay of hydrogels: Set different concentration gradients of the samples to be tested as follows: Gel: 2.5, 5, 10, 10, 40μg / mL; Fe3O4 nanoparticles: 6.25, 12.5, 25, 50, 100 μg / mL; Idarubicin: 0.00125, 0.0025, 0.005, 0.01, 0.02 μg / mL.
[0051] The CCK8 experiment was used to verify the effect of co-culture of Gel, Fe3O4 nanoparticles, and IDA on the proliferation ability of rat liver cancer cell line N1S1. The specific steps include: (1) Fe3O4 nanoparticles were sterilized by UV for 24 h and then resuspended in complete culture medium to a series of concentration gradients: 6.25, 12.5, 25, 50, 100 μg / mL, Gel preparation was 2.5, 5, 10, 10, 40 μg / mL, IDA 0.00125, 0.0025, 0.005, 0.01, 0.02 μg / mL. Set aside.
[0052] (2) Cultivate N1S1 cells until the logarithmic growth phase, resuspend in complete medium, count the cells, and adjust the density to 5×10 4 cells / mL and added into a 96-well plate at 100 μL / well.
[0053] (3) When the cells grow to the point of being attached to the wall, add drugs so that the drug concentration in each well reaches the above preset concentration gradient. Set up 6 replicate wells for each group and set up a control group.
[0054] (4) Place the cells in a cell culture incubator, away from light and at a constant temperature.
[0055] (5) After culturing for 24 and 48 h, respectively, remove the culture medium in each well and replace it with an equal volume of fresh complete culture medium. Then, add 10 μL of CCK8 liquid to each well and continue incubating in the incubator in the dark for 1-2 h.
[0056] (6) Use an enzyme-linked immunosorbent assay to read the optical density (OD) of the solution system in each well at 450 nm.
[0057] (7) Cell Viability (CV) was calculated using the following formula: CV = (OD test -OD blank ) / (OD control -OD blank ).
[0058] The results are as follows Figure 6As shown, with the increase of idarubicin concentration, cell viability began to decline, while the cells of Gel and Fe3O4 nanoparticles were almost completely alive, and with the increase of the concentration of the tested sample, the cell viability remained basically unchanged, indicating that Gel and Fe3O4 nanoparticles had no obvious toxicity, and thus the composite gel Fe3O4-Gel had no obvious toxicity.
[0059] Example 5 Coagulation and hemolysis experiments of hydrogels: Blood samples were collected, sodium citrate was used to prevent blood coagulation, the blood samples were diluted to an appropriate ratio, and then different concentrations of Gel and Fe3O4 nanoparticles were added to observe the changes in coagulation. The specific steps of the experiment are as follows: 1. Coagulation test (1) Gel and Fe3O4 nanoparticles were sterilized by UV for 24 h and then resuspended in PBS to a series of concentration gradients: 2.5, 5, 10, 10, 40 μg / mL and 6.25, 12.5, 25, 50, 100 μg / mL, and added to a 96-well plate at 50 μL / well.
[0060] (2) Take 400 μL of calcium chloride solution (CaCl2, 0.1 M) and mix it with 3600 μL of citrated fresh rat tail vein blood. Vortex for 10 s and then add 50 μL / well to a 96-well plate to allow it to fully mix and react with the above system.
[0061] (3) Wash the corresponding wells three times with PBS at 1, 3, 5, 7, and 10 min in sequence to terminate the reaction, remove the soluble blood substances, and take photos for record.
[0062] 2. Hemolysis test (1) Gel and Fe3O4 nanoparticles were sterilized by UV for 24 h and then resuspended in PBS to a series of concentration gradients of 2.5, 5, 10, 10, 40 μg / mL and 6.25, 12.5, 25, 50, 100 μg / mL. Two control groups were set up: PBS as the negative control group and deionized water as the positive control group.
[0063] (2) Fresh rat tail vein blood was centrifuged at 3000 rpm for 5 min and washed with PBS several times until the supernatant became clear. The supernatant was discarded to obtain fresh red blood cell pellet, which was then diluted 50 times with PBS.
[0064] (3) Mix equal volumes of 1 mL of the above-mentioned Gel and Fe3O4 nanoparticles and 1 mL of diluted red blood cell suspension, place them in a 2 mL EP tube, and incubate them in a 37 ℃ incubator for 2 h.
[0065] (4) Centrifuge at 1000 rpm for 5 min, take the supernatant, add 100 μL / well to a 96-well plate, and read the OD value of each well at 570 nm using a microplate reader.
[0066] (4) The hemolysis rate is calculated by the following formula: Hemolysis rate = (OD test -OD blank ) / (OD control -OD blank ).
[0067] Depend on Figure 7 As shown in the figure, the concentration of 0 is the blank group, and the coagulation time of each group of gel is basically the same as that of the blank group, indicating that the material has little effect on the blood coagulation function and has good blood compatibility. Figure 8-9 As shown in the figure, by comparing the color of the supernatant and the hemolysis rate of gels of different concentrations, a hemolysis rate exceeding 5% is considered hemolysis. The hemolysis rates of Gel and Fe3O4 nanoparticles are both lower than 5%, indicating that Gel and Fe3O4 nanoparticles have good blood compatibility, and thus the composite gel Fe3O4-Gel prepared from Gel and Fe3O4 nanoparticles also has good blood compatibility.
[0068] In summary, the present invention provides a temperature-sensitive hydrogel that can be used for TACE treatment of liver cancer. The raw materials for its preparation are mainly hydrogel made from Poloxamer-407 and Fe3O4 nanoparticles. Through physical cross-linking between the raw materials, the prepared temperature-sensitive hydrogel is basically non-toxic and can be used as an embolic material for transhepatic arterial chemoembolization. It can not only achieve intravascular embolism but also has degradability, avoiding permanent embolism in the blood vessel, which is beneficial to the development of liver cancer treatment technology.
[0069] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. Application of a temperature-sensitive hydrogel in the preparation of anti-tumor drugs, contrast agents or vascular embolization products.
2. The use according to claim 1, characterized in that: The vascular embolization product is a product for treating liver cancer through hepatic arterial chemoembolization.
3. The use according to claim 1, characterized in that: The raw materials for preparing the temperature-sensitive hydrogel include Poloxamer-407 and Fe3O4 nanoparticles, wherein the particle size of the Fe3O4 nanoparticles is 15 nm-20 nm.
4. A method for preparing a temperature-sensitive hydrogel, characterized in that: include: First, Poloxamer-407 is used to prepare a hydrogel with a concentration of 10 wt%-20 wt%, and then the hydrogel is evenly mixed with a Fe3O4 suspension to obtain a composite gel.
5. The preparation method according to claim 4, characterized in that: The volume ratio of the hydrogel to the Fe3O4 suspension is 1:
10.
6. The preparation method according to claim 4, characterized in that: The Fe3O4 suspension is prepared by suspending Fe3O4 nanoparticles in water, with a concentration of 1 mg / mL.
7. The preparation method according to claim 4, characterized in that: The particle size of the Fe3O4 nanoparticles is 15 nm-20 nm.
8. An injectable material, characterized in that: The invention relates to a temperature-sensitive hydrogel prepared by the preparation method according to any one of claims 4 to 7.
9. The injectable material according to claim 8, characterized in that Pharmaceutically acceptable excipients are also included.
10. An embolic agent, characterized in that: The invention relates to a temperature-sensitive hydrogel prepared by the preparation method according to any one of claims 4 to 7.
Citation Information
Cited By
Injectable temperature response enhanced composite dual-network magnetic particle gel as well as preparation method and application thereof
CN120437363A